Assembly of a M4L4 "folded-cube" using a T-shaped, right-angled ligand. Issue 3 (2nd December 2014) - Elguraish, Ismail; Zhu, Kelong; Hernandez, Leslie A.; Amarne, Hazem; Luo, Jingwei; Vukotic, V. Nicholas; Loeb, Stephen J.
Abstract : A new bipyridine ligand based on a T-shaped 2, 4, 7-trisubstituted benzimidazole framework was synthesised. When combined with [Pt(dppp )] 2+ corners, eight right angles (four metal and four ligand) combine to form a M4 L4 cluster with an unusual folded-cube structure. Abstract : A new bipyridine ligand based on a T-shaped 2, 4, 7-trisubstituted benzimidazole framework was synthesized with a 90° angle between the two nitrogen donors. When combined with convergent [Pt(dppp )] 2+ corners, eight right angles (four metal and four ligand) combine to form a M4 L4 cluster with an unusual folded-cube structure.